Asuhan Kebidanan Komprehensif Pada Ny. U di Praktik Mandiri Bidan Intan Angraini Kota Jambi Tahun 2026 - Ayu Oktoviani; Sinta Kartika Sari; Mutiara Lisna Putri (JOURNAL OF MIDWIFERY SCIENCE, 2026)
Continuity of Care (COC) in midwifery involves providing comprehensive care spanning pregnancy, childbirth, the postpartum period, and newborn care through to family planning services. Such comprehensive care is crucial for the early detection of risk factors and the prevention of complications that could otherwise increase maternal and infant morbidity and mortality rates. The objective of this report is to outline the comprehensive midwifery care provided to Mrs. U at the Independent Midwifery Practice of Intan Angraini, S.Keb, in Jambi City in 2026, utilizing the midwifery management approach and SOAP documentation. A descriptive case study method employing the Continuity of Care approach was used. The subject of this case study was Mrs. U, who received care ranging from the third trimester of pregnancy through childbirth, the postpartum period, and newborn care to family planning services. Data collection was conducted via anamnesis, observation, physical examinations, diagnostic tests, and document review. The care outcomes indicated that Mrs. U pregnancy proceeded normally without complications. Childbirth occurred spontaneously and physiologically, the postpartum period progressed normally, the newborn was healthy, and the mother selected a contraceptive method suited to her needs. Continuous midwifery care effectively improved maternal and infant health and prevented complications. It is concluded that the implementation of comprehensive midwifery care using the Continuity of Care approach facilitates optimal service delivery, enhances maternal and infant health quality, and supports efforts to reduce maternal and infant mortality rates.